Peran Literasi Keuangan dan Modal Sosial dalam Meningkatkan Kinerja Keuangan Bumdes: Studi Kasus di Kabupaten Boalemo - Sri Putri Inggriyani Nihali; Herlina Rasjid; Srie Isnawaty Pakaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the partial and simultaneous effects of financial literacy and social capital on the financial performance of Village-Owned Enterprises (BUMDes) in Boalemo Regency. Using a quantitative approach and multiple linear regression analysis, data were collected through questionnaires from 82 administrators representing 41 active BUMDes, selected via purposive sampling. Hypothesis testing using the t-test revealed that both financial literacy (t = 3.721, p = 0.000) and social capital (t = 4.112, p = 0.000) have a positive and significant partial effect on financial performance. Simultaneously, the F-test (F = 25.876, p = 0.000) confirms that both variables jointly significantly influence financial performance. The coefficient of determination (R² = 0.563) indicates that 56.3% of the variance in BUMDes' financial performance is explained by the combined influence of financial literacy and social capital. The remaining 43.7% is attributed to other factors outside this model. The study concludes that strengthening the financial literacy of administrators and fostering social capital—characterized by community networks, trust, and cooperative norms—are critical, synergistic strategies for enhancing the financial accountability and operational success of BUMDes. These findings offer a systemic management perspective beyond mere technical accounting solutions.